Konsep Pendidikan Keagamaan Menurut Paku Buwana IV - Purwadi Purwadi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
This research describes religiosity education of Javanese in Serat Wulangreh. According to this traditional popular literature that created by Sunan Paku Buwana IV at Kraton Surakarta Hadiningrat, everyone who studies Islam Religion has to get the four principles. They are Qur’an, Hadis, Ijma’ and Qiyas. Perfectly Islamic studies, one can ask to teacher who has wide knowledge.In practice, Serat Wulangreh gives advice so that mean always do akhlakul karimah or good behaviour.